FAKTOR KARAKTERISTIK YANG BERHUBUNGAN DENGAN KEPUASAN PASIEN PADA LAYANAN PERSALINAN DI PUSKESMAS KABUPATEN GROBOGAN - Yunita Widyastuti; Priyadi Nugraha Prabamukti; Zahroh Shaluhiyah (Fakultas Kesehatan Masyarakat Universitas Diponegoro, 2018)
Customer service and customer satisfaction are the core of a business, as well as services to patients provided by hospitals or other healthcare organizations. Therefore the motion of healthcare business should lead to customer satisfaction. Patient is a customer who has the right to specify requirements for products or services provided by the organization. Customer satisfaction will be achieved if the product or service provided is a response to customer needs. The purpose of this study is to determine the characteristic factors associated with patient satisfaction in delivery services at Grobogan healthcare. This research used descriptive analytic method with cross sectional design. The sample of this research was 100 respondents. Data analysis included univariate analysis with presentation of frequency distribution table and bivariate analysis using Slovin. The univariate result showed that the satisfaction of customer / patient of delivery health service at healthcare in Grobogan Regency tended not to be satisfied (77%). Most respondents were dominated by patients of adult age group 26-45 years old (74%) and low-educated (77%). The result of bivariate analysis showed that there was a significant correlation on service type variables (p = 0,040) and disease history factor (p = 0,043). Suggestion writer in this research that healthcare had to improve supervision both internal and external, giving sanction for officer who was not perform task according to SOP.